2016
DOI: 10.22502/jlmc.v4i2.90
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Sensitivity in Post Cesarean Surgical Site Infection at a Tertiary Care Centre in Eastern Nepal

Abstract: Introduction: Post cesarean surgical site infection (SSI) is one of the common complications diagnosed in 2.5%-16% of the cases and is associated with significant increase in maternal morbidity, hospital stay, costs, and psychological stress to the new parents. This study was designed to study the incidence of SSI and the antimicrobial resistance pattern in our hospital.   Methods: This was a prospective observational study conducted from July 2015 to December 2015, in which all patients who were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
4
2
2
Order By: Relevance
“…However, in contrast to our findings, they recorded 50.7% susceptibility to tetracycline by S. aureus in their report on antimicrobial susceptibility pattern of Staphylococcus aureus in patients with surgical site infection at Debre Markos Referral Hospital, Amhara Region, Ethiopia. Also, in contrast to our findings of 83.3% Staphylococcus aureus susceptibility to ciprofloxacin, Chhetry et al [20], in Nepal reported 86.2% Staphylococcus aureus resistance of ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to our findings, they recorded 50.7% susceptibility to tetracycline by S. aureus in their report on antimicrobial susceptibility pattern of Staphylococcus aureus in patients with surgical site infection at Debre Markos Referral Hospital, Amhara Region, Ethiopia. Also, in contrast to our findings of 83.3% Staphylococcus aureus susceptibility to ciprofloxacin, Chhetry et al [20], in Nepal reported 86.2% Staphylococcus aureus resistance of ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 99%
“…However their findings of 100% resistance of gentamycin by Klebsiella spp varies with our report of 75% resistance. Also in a justification of our findings of very high resistance to commonly used antibiotics by gram negative organisms, Chhetry et al [20], in Nepal reported 80% ciprofloxacin and erythromycin resistance and 100% cotrimoxazole resistance by E. coli while a 100% ciprofloxacin and erythromycin resistance by Klebsiella spp was also recorded.…”
Section: Discussionsupporting
confidence: 62%
“…The overall rate of culture-con rmed post-caesarean wound infections observed in the current study was 85.78% and is consistent with the reports from Kuwait (75.7%) [23], Nepal (74.75%) [24] and Uganda (85%) [25]. However, it was slightly higher than the results of earlier studies reported from Nigeria (92.2%) [19] and Cameroon (96%) [26].…”
Section: Discussionsupporting
confidence: 90%
“…We have observed very low resistance of imipenem and netilmicin this might be due to limited exposure of these antibiotics because of their expensiveness. Among gram-positive isolates (Staphylococcus aureus & coagulase negative staph) penicillin group of antibiotics was shown high resistance in the current study accordance to Walelign et al 34 Very high incidence of MRSA (76.8%) reported in our study compatible to Rijal et al 35 showed 75.5% MRSA contrary to that Chhetri M. et al (36) reported 58.6% MRSA on their study. Overall Imipenem was the most sensitive and amoxicillin/ clavulanate was the most resistant antibiotic in our study similar findings were observed by Ezat H et al 37…”
Section: Antimicrobial Resistance Patternsupporting
confidence: 86%